2014
DOI: 10.1037/a0032632
|View full text |Cite
|
Sign up to set email alerts
|

Externalizing behavior problems among polydrug cocaine-exposed children: Indirect pathways via maternal harshness and self-regulation in early childhood.

Abstract: This study examined direct and indirect associations between prenatal cocaine exposure (CE) and children’s externalizing problems in kindergarten via higher maternal harshness and lower self-regulation in early childhood. Other environmental risk variables such as child exposure to community violence and experience of hunger were used as additional predictors. The sample consisted of 216 mother-infant dyads recruited at delivery from local area hospitals (116 cocaine-exposed, 100 non-exposed). Maternal harshne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 109 publications
(169 reference statements)
2
16
0
Order By: Relevance
“…However, the frequent co‐occurrence of prenatal and postnatal exposures (Astley, ; Astley et al, ; Gibbard, ; Hyter, ; Koponena et al, ) suggests that models should incorporate both time periods. In addition to the small number of studies that have examined interactions between PAE and other prenatal exposures (Price et al, ), a few studies outside the PAE literature have examined the combined effects of prenatal cocaine exposure and postnatal adversity on development (Eiden, Coles, Schuetze, & Colder, ; Eiden, Godleski, Colder, & Schuetze, ; Eiden, Granger, Schuetze, & Veira, ; Liebschutz et al, ) or the differential impacts of stress during prenatal and postnatal periods (Jensen et al, ; Jensen et al, ). Together, this literature highlights the importance of incorporating information from both prenatal and postnatal periods into the assessment of individual exposure profiles.…”
Section: Introductionmentioning
confidence: 99%
“…However, the frequent co‐occurrence of prenatal and postnatal exposures (Astley, ; Astley et al, ; Gibbard, ; Hyter, ; Koponena et al, ) suggests that models should incorporate both time periods. In addition to the small number of studies that have examined interactions between PAE and other prenatal exposures (Price et al, ), a few studies outside the PAE literature have examined the combined effects of prenatal cocaine exposure and postnatal adversity on development (Eiden, Coles, Schuetze, & Colder, ; Eiden, Godleski, Colder, & Schuetze, ; Eiden, Granger, Schuetze, & Veira, ; Liebschutz et al, ) or the differential impacts of stress during prenatal and postnatal periods (Jensen et al, ; Jensen et al, ). Together, this literature highlights the importance of incorporating information from both prenatal and postnatal periods into the assessment of individual exposure profiles.…”
Section: Introductionmentioning
confidence: 99%
“…Eiden and colleagues (2013) noted that the link between witnessing violent acts and increased behavior problems in preschool children is well established. Results indicated community violence as one of the predictors of problem behaviors in their sample (Eiden et al, 2013). Vanfossen, Brown, Kellam, Sokoloff, and Doering (2010) found neighborhood violence was a salient factor in the development of aggression in boys and girls, primarily during the transition from primary school into middle school.…”
Section: Introductionmentioning
confidence: 97%
“…The importance of postnatal factors was demonstrated in a study of children exposed to heroin during pregnancy, which found that children adopted at a young age had intellectual skills similar to non-exposed controls; however, heroin-exposed children who remained with their biological parents had lower intellectual test scores compared to non-exposed controls (19). In another study, toddlers prenatally exposed to polysubstance use were found to have adverse outcomes, such as lower self-regulation and increased externalizing problems at 3 years of age, when their mothers were observed using harsh behaviors during a video-taped free play paradigm (20). Heightened infant reactivity and distress, mother-infant attachment disorders, and decreased sensitivity and responsiveness towards the child have been associated in research with parenting practices among mothers with various substance use disorders (2126).…”
Section: Introductionmentioning
confidence: 99%